2018
DOI: 10.11144/javeriana.sc23-3.cpop
|View full text |Cite
|
Sign up to set email alerts
|

Cellulases production on paper and sawdust using native Trichoderma asperellum

Abstract: Microbial cellulases are industrially used enzymes that catalyze the cleavage of the glycosidic bonds of cellulose. This hydrolysis yields sugars that can be used in processes such as bioethanol production. These enzymes are mainly produced by fungi belonging to the genus Trichoderma via submerged or solid state fermentation with cellulosic materials as substrates. Recent publications have increasingly demonstrated that alternatives to T.reesei enzymes in the production of second generation biofuels exist. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
(34 reference statements)
0
3
0
1
Order By: Relevance
“…Zapata et al observed that Trichoderma asperellum and Trichoderma reesei colonies grow larger on sawdust that is supplemented with yeast extract and peptone. These media modi cations have also altered T. reesei morphology with denser and highly branched mycelia, causing larger surface area for enzyme-substrate interaction and resulting an elevated enzyme production (Zapata et al, 2018). The increase of solid loading during SSF leads to an increase of ethanol production as reported by Passadis et al Higher solids loadings imply higher carbohydrates loading, higher glucose production and higher ethanol production (Passadis et al, 2022)…”
Section: Effect Of Substrate and Nutrients Supplementationmentioning
confidence: 90%
See 1 more Smart Citation
“…Zapata et al observed that Trichoderma asperellum and Trichoderma reesei colonies grow larger on sawdust that is supplemented with yeast extract and peptone. These media modi cations have also altered T. reesei morphology with denser and highly branched mycelia, causing larger surface area for enzyme-substrate interaction and resulting an elevated enzyme production (Zapata et al, 2018). The increase of solid loading during SSF leads to an increase of ethanol production as reported by Passadis et al Higher solids loadings imply higher carbohydrates loading, higher glucose production and higher ethanol production (Passadis et al, 2022)…”
Section: Effect Of Substrate and Nutrients Supplementationmentioning
confidence: 90%
“…There were signi cant differences which were discovered between untreated and heat-treated biomass, such as sterilization stage that eliminated the contamination of other microorganisms present in the biomass, thus increasing the growth of microorganism in interest. Zapata et al reported that enzymes activity was low when sawdust was utilized as a substrate for SSF and it was suggested that the deligni cation of sawdust prior to SSF with Trichoderma should be studied thoroughly as lignin is the main challenge for enzyme production (Zapata et al, 2018). Silva et al evaluated three different pretreatments to optimize the enzymatic hydrolysis of carnauba biomass, namely hydrothermal (HT), alkaline (AL), and alkaline acid (AA) pretreatment.…”
Section: Utilization Of Lignocellulosic Wastes As Substratementioning
confidence: 99%
“…T. asperellum has been shown to produce hydrolytic enzymes such as cellulase and xylanase [2 , 3] . T. asperellum has also been reported to hydrolyse wheat bran, wheat straw, paper, sawdust, corncob, duckweed, and agave by secreting cellulases [2] , [3] , [4] , [5] , [6] , [7] . Strain PK1J2 has been proven to be capable of producing high cellulase.…”
Section: Data Descriptionmentioning
confidence: 99%
“…The studied microorganisms were consistently subjected to physical and chemical mutagenic effects to enhance their cellulolytic properties. The technique used to induce mutagenesis is described hereafter and was created based on those presented in [20,[26][27][28][29][30] and adapted to the existing conditions.…”
Section: Induced Mutagenesis Of Microorganismsmentioning
confidence: 99%